Hardware Configuration for AutoCAD, Revit, and Inventor. - Bryant, Shaun (linkedin.com, 2020)
Autodesk software such as AutoCAD and Revit can place heavy demands on your machine. Learn about hardware options that can help you make the most of your CAD workstation.